Coordination of humanitarian logistic model plan for natural disaster in East Java, Indonesia - Tanti Octavia; Carolina Halim; I Gede A.Widyadana; Herry Palit (International Journal of Supply Chain Management, 2016)
Natural disasters in Indonesia often resulted in huge casualties and material lost. Therefore, the coordination of humanitarian logistic is important to be upgraded. The result of this research is a model plan of humanitarian logistic coordination in East Java with case study in Pasuruan regency. The simulation of dynamic system model is run using Vensim software. The objective function is to minimize the response time for emergency response. The proposed model involves Indonesia Red Cross (IRC) as a core team in humanitarian logistic in East Java. The order of priority that could be considered is the assessment team only conducted by IRC, addition of IRCs doctors, addition of IRCs boats for evacuation, additions of IRCs personnel for soup kitchen, and addition of IRCs boats for aid distribution. The simulation results show that the proposed model can reduce the response time up to 20 hours.